Continuous Training, Job Satisfaction and Gender: An Empirical Analysis Using German Panel Data - Claudia Burgard; Katja Görlitz (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
Using data from the German Socio-Economic Panel (SOEP), this paper analyzes the relationship between training and job satisfaction focusing in particular on gender differences. Controlling for a variety of socio-demographic, job and firm characteristics, we find a difference between males and females in the correlation of training with job satisfaction which is positive for males but insignificant for females. This difference becomes even more pronounced when applying individual fixed effects. To gain insights into the reasons for this difference, we further investigate training characteristics by gender. We find that financial support and career-orientation of courses only seems to matter for the job satisfaction of men but not of women.
Keywords: I29; J24; J28; M53; 330; Training; job satisfaction; gender differences; fixed effects; Weiterbildung; Arbeitszufriedenheit; Geschlecht; Frauenbildung; Schätzung; Deutschland